2007
DOI: 10.3174/ajnr.a0744
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging in Patients With Essential Tremor

Abstract: BACKGROUND AND PURPOSE:The traditional paradigm has regarded essential tremor (ET) as a benign disorder. However, recent clinical, neuroimaging, and neuropathologic studies suggest that ET may be a progressive neurologic disorder. Based on clinicopathologic findings that cerebellum and its outflow are the key structures in ET and degeneration of gray matter in cerebellum is followed by consequent wallerian degeneration of white matter (WM) fibers, the aim of the present study was to investigate changes in anis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
103
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 17 publications
3
103
1
2
Order By: Relevance
“…Importantly, areas that correlate with objective tremor measures extend to the midbrain, specifically areas around the cerebral peduncles and red nucleus thus including the WM within dentate‐rubro‐olivary pathway (Guillain‐Mollaret triangle), which is considered a tremorgenic loop (Murdoch, Shah, & Jampana, 2016). These findings are consistent with previous studies showing abnormalities in DTI parameters directly within red nucleus (Jia et al., 2011), in retrorubral WM (Shin, Han, Kim, & Lee, 2008) and the Guillain‐Mollaret triangle (Nicoletti et al., 2010) in ET patients. However, no correlation with tremor clinical parameters was reported in these studies (Jia et al., 2011; Nicoletti et al., 2010; Shin et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, areas that correlate with objective tremor measures extend to the midbrain, specifically areas around the cerebral peduncles and red nucleus thus including the WM within dentate‐rubro‐olivary pathway (Guillain‐Mollaret triangle), which is considered a tremorgenic loop (Murdoch, Shah, & Jampana, 2016). These findings are consistent with previous studies showing abnormalities in DTI parameters directly within red nucleus (Jia et al., 2011), in retrorubral WM (Shin, Han, Kim, & Lee, 2008) and the Guillain‐Mollaret triangle (Nicoletti et al., 2010) in ET patients. However, no correlation with tremor clinical parameters was reported in these studies (Jia et al., 2011; Nicoletti et al., 2010; Shin et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous studies showing abnormalities in DTI parameters directly within red nucleus (Jia et al., 2011), in retrorubral WM (Shin, Han, Kim, & Lee, 2008) and the Guillain‐Mollaret triangle (Nicoletti et al., 2010) in ET patients. However, no correlation with tremor clinical parameters was reported in these studies (Jia et al., 2011; Nicoletti et al., 2010; Shin et al., 2008). Our data show a unique correlation of CST changes exclusively with combined TremScore but not with frequency or FTM scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Based on reduced fractional anisotropy in the pons, cerebellum, and midbrain and extensive WM damage in the frontal cortex and temporoparietal regions in patients with ET, others proposed that an abnormality in the cerebellothalamocorticocerebellar loop is responsible for the tremor. 46 Similarly, compromised WM has been reported in frontoparietal regions, cerebral hemispheres, the thalamus, and brain stem. 42 In summary, with the exception of 1 study, 43 most DTI research in ET demonstrated that widespread disintegrity of cerebral and cerebellar fiber tracts is common and likely underlies tremor generation.…”
Section: -3540-42mentioning
confidence: 99%
“…42 In summary, with the exception of 1 study, 43 most DTI research in ET demonstrated that widespread disintegrity of cerebral and cerebellar fiber tracts is common and likely underlies tremor generation. [40][41][42]46 Although it is known that DTI measures are indicators for WM integrity, the exact nature underlying these pathologic processes is unknown. Whether demyelination, myelin injury, neuronal loss, or other processes underlie abnormal DTI values in patients with ET remains to be ascertained.…”
Section: -3540-42mentioning
confidence: 99%